Kohlschutter–Tonz syndrome: clinical and genetic insight on patients with ROGDI variant - Osama Y. Muthaffar; Lina M. Abdulrahman; Anas S. Alyazidi; Taif K Alotibi (Journal of Biochemical and Clinical Genetics)
Background: Kohlschutter–Tonz syndrome (KTS) is a rare genetically heterogeneous autosomal recessive syn drome initially described in 1974 and characterized by the triad of infantile-onset epilepsy, amelogenesis imperfecta, and developmental delay. KTS patients share a common genetic trait, namely a variant in the ROGDI gene, a gene of unknown function that maps to chromosome 16p13.3. Methods: Following appropriate ethical and logistical measures, we reviewed literature cases with the ROGDI variant and presented one novel case diagnosed using whole exome sequencing. Clinical, genetic, developmental, and radiological data were reviewed and compared accordingly. Results: There were 22 studies involving the ROGDI variant, including one additional novel case we reported. Thirteen patients were males, and ten were females. The current age range was 2–24 years. The majority of patients had their first seizure episode between 6 and 12 months. Birth parameters were within normal limits. The majority had unspecified forms of seizures, followed by generalized tonic-clonic and focal tonic-clonic seizures with secondary generalization. Patients with controlled seizures were likely on leveti racetam. Amelogenesis imperfecta and yellowish teeth were distinctive hallmarks. Behavioral problems were observed in one-third of the cases. Electroencephalogram (EEG) and magnetic resonance imaging (MRI) were abnormal in nearly one-third of the cases. Conclusion: Identifying and drawing conclusive evidence for patients with the ROGDI variant was challenging. Conflicting reports on the efficacy of different anti-seizure medications and the adequate treatment modalities were observed. Potential hallmarks continue to be established. Current evidence can be validated, and a delineation of clinical and molecular findings can be achieved with additional cases. [JBCGenetics 2024; 7(1.000): 012-020]